Electroacupuncture Suppresses CCI-Induced Neuropathic Pain through GABAA Receptors. (7th October 2022) - Li, Sisi; Jiang, Xia; Wu, Qiaoyun; Jin, Yun; He, Rong; Hu, Jie; Zheng, Yuyin
Abstract : Neuropathic pain remains a chronic and intractable pain. Recent studies have shown a close relationship between gamma-aminobutyric acid A (GABAA) receptor and neuropathic pain. Spinal cord GABAA receptors are key modulators of pain processing. Electroacupuncture (EA) is currently used worldwide to relieve pain. The immunomodulatory effect of EA in animals has been proposed in previous studies. However, it remains unclear how EA contributes to alleviating neuropathic pain. In this study, the chronic constriction injury (CCI) rat model was used to explore the relationship between GABAA receptor and neuropathic pain. We also investigated whether EA treatment could ameliorate pain hypersensitivity by modulating the GABAA receptor. To determine the function of EA in neurological diseases, in this study, the mechanical withdrawal threshold (MWT) and thermal withdrawal latency (TWL) were assessed to determine the threshold of pain. In addition, we used Western blot, immunofluorescence, and real-time quantitative PCR to confirm whether EA treatment relieves pain hypersensitivity by regulating GABAA receptors. The morphology of synapse was examined using an electron microscope. In the present study, EA relieved mechanical allodynia and thermal hyperalgesia. EA also inhibited microglial activation in the spinal cord, accompanied by increased levels of GABAAR α 2, GABAAR α 3, and GABAAR γ 2 subunits. However, the analgesic effect of EA was attenuated by treatment with the GABAA receptor antagonist bicuculine. Overall, the present results indicate that microglia and GABAA receptor might participate in EA analgesia. These results contribute to our understanding of the impact of EA on rats after sciatic nerve compression, providing a theoretical basis for the clinical application of EA analgesia.